28 THE REGULATION OF NEURONAL OUTGROWTH AND RETRACTION BY SEROTONIN RECEPTORS 5-HT4a AND 5-HT7: THE ROLE OF LIM KINASE 1. (1st March 2006) - Krbanjevic, A.; Liu, G.; Profirovic, J.; Voyno-Yasenetskaya, T.
Abstract : Serotonin is a neurotransmitter with a prominent role in the central nervous system. The higher mammals express seven families of serotonin receptors. Functions of only some of the receptors have been determined. Most of the 5-HT functions are mediated through G protein-coupled receptors. We have shown that 5-HT4a serotonin receptor couples GaS and Ga13 protein, causing RhoA-dependent neurite retraction and cell rounding (Ponimaskin et al, 2002). We also found that 5-HT7 serotonin receptor couples to Gas and Ga12 protein. 5-HT7 receptor-Ga12 protein pathway induces activation of two small GTPases, RhoA and Cdc42, leading to pronounced cell rounding and filopodia formation, respectively (Kwachnina et al, 2005). LIM kinase 1 (LIMK1) is a serine-threonine kinase that negatively regulates function of actin depolymerizing protein cofilin. Therefore, activation of LIMK1 leads to actin polymerization. The small GTPases of Rho family are shown to stimulate LIMK1. In the present study, we are showing for the first time that 5-HT4a and 5-HT7 receptor phosphorylate LIMK1. Therefore, this could be mechanism for regulation of cytoskeleton of cells transfected with 5-HT4a and 5-HT7 receptors. When we down-regulated endogenous LIMK1 using siRNA technology we almost totally lost rounded cells. Also, when we cotransfected 5-HT4a R and 5-HT7 receptor with LIMK1-siRNA, we observed that the 5-HT7 receptor led to an increase in the number of rounded cells and a decrease in the number of process-bearing cells. We are suggesting here that LIMK1 influences activity of small GTPases through the feedback loop between LIMK1 and small GTPases. This mechanism is important for precise control of LIMK1 activity in cells transfected with 5-HT4a and 5-HT7 receptors. Our data give a new insight into serotonin, not only as a well-known neurotransmitter but also as a modulator of neuronal plasticity.